Case Report: A Severe SARS-CoV-2 Infection in a Teenager With Angelman Syndrome - Lopes, Alessandra G. D.; Celestino, Camila S. H.; Barros, Tiago T. A.; Fevereiro, Aline G.; Gejer, Debora H.; Oliveira, Fernando M. F.; Brasil, Jamile M.; Bossolan, Rosely M.; Pinto, Gabriela C. C.; Santos, Ana C. E. Z.; Divan, Luis A.; Alves, Ingrid A. B.; et al. (Frontiers in Medicine, 2021)
Teenagers have generally presented mild to no symptoms of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. We present the case of a 14-year-old teenager with Angelman syndrome (AS) who presented severe COVID-19 symptoms. He has spent 20 days in the ICU, with elevated levels of inflammatory biomarkers (C-reactive protein and D-dimer) and increased peaks of neutrophil-to-lymphocyte ratio, which is uncommon for teenagers diagnosed with COVID-19. Although the physiological instability observed in the patient, he was able to produce neutralizing antibodies, suggesting functional immune response. The literature concerning the immune response to infections in AS is still poor and to our knowledge, this is the first report of AS patient diagnosed with COVID-19. Therefore, this study can alert other AS patients or other rare diseases that might lack of immune response information and could suffer severe consequences of the SARS-CoV-2 infection.